2012
DOI: 10.1038/modpathol.2011.220
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of endometrial intraepithelial neoplasia diagnosis is good, but influenced by the diagnostic style of pathologists

Abstract: Endometrial intraepithelial neoplasia (EIN) applies specific diagnostic criteria to designate a monoclonal endometrial preinvasive glandular proliferation known from previous studies to confer a 45-fold increased risk for endometrial cancer. In this international study we estimate accuracy and precision of EIN diagnosis among 20 reviewing pathologists in different practice environments, and with differing levels of experience and training. Sixty-two endometrial biopsies diagnosed as benign, EIN, or adenocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
(38 reference statements)
0
19
0
4
Order By: Relevance
“…We showed that pathologists had diagnostic "styles" (30). This is shown in Figure 1 where pathologists fell into two style groups: one had a tendency to push SIL and CIN diagnoses to a higher grade -a diagnostically aggressive group, whereas the other was more conservative.…”
Section: Discussionmentioning
confidence: 85%
“…We showed that pathologists had diagnostic "styles" (30). This is shown in Figure 1 where pathologists fell into two style groups: one had a tendency to push SIL and CIN diagnoses to a higher grade -a diagnostically aggressive group, whereas the other was more conservative.…”
Section: Discussionmentioning
confidence: 85%
“…Correspondingly, normal secretory glands late in the menstrual cycle can develop redundant secretory epithelium within gland tracts that may be closely apposed, at quite high density. Coordinated changes in cytology and architecture must be demonstrated to maintain specificity of EIN diagnosis in a 15 and the high concordance between the two reviewers in this study make the possibility of misdiagnosis unlikely. Limitations of our study include relatively short follow-up of a modest number of patients, and lack of a formally matched secretory-free comparison group.…”
Section: Discussionmentioning
confidence: 87%
“…DSÖ endometrial hiperplazi sınıflamasını yapan grubun içinde bulunan kurman'ın kendi ekibinin yaptığı uyum çalışmasında bile en can alıcı kategori olan atipik hiperplazi (kanser öncülü olduğundan hastada tedavi yöntemi değiştirir o nedenle klinik öneme sahiptir) gözlemcilerden en düşük uyumu almıştır (10). endometrial hiperplazileri moleküler patogenezini göz önüne alarak morfolojik kriterler geliştirilen "endometrial intraepitelyal neoplazi" (eın) sınıflamasında ise uyum daha yüksektir (11). Bunun nedeni tanı verilerken bazı özgün kriterlerin kullanılmış olmasıdır (12).…”
Section: Tanısal Uyumsuzluğun Kökenleri Nerededir?unclassified
“…Bunun nedeni tanı verilerken bazı özgün kriterlerin kullanılmış olmasıdır (12). Bir önceki sınıflandırma atipi için bez sayısının artışından söz ederken eın sınıflandırması %50'den fazla artış kriteri, yine DSÖ sınıflandırmasında atipik hücrenin morfolojik tarifi yapılırken eın sınıflamasında normal bez ile karşılaştırma kriteri getirilmiştir, bu kriterler yoruma yer bırakmayacak şekilde morfolojik sınırları daha kesin olarak tanımladığından gözlemciler arası uyumu yükseltmiştir (11).…”
Section: Tanısal Uyumsuzluğun Kökenleri Nerededir?unclassified
See 1 more Smart Citation